O estresse oxidativo em pacientes hemodialisados e a influência do tratamento terapêutico - Schmitt, Gabriela Cristina (2006)
The imbalance between the oxidant species formation and the activity of antioxidants is known as oxidative stress and it is directly related to the etiology and/or the progression of chronic diseases such as chronic renal failure (CRF), atherosclerosis and cardiovascular diseases. The CRF can be the result of variety renal injuries that lead to toxic substances accumulation and metabolic disturbances in the organism. Patients with chronic renal disease on hemodialysis treatment, whose main cause of morbi-mortality is the cardiovascular diseases, are constantly under oxidative stress by the uremic condition, but overall by the hemodialysis treatment, which leads to an increase of reactive species and decrease of antioxidant defenses. Moreover, these patients also present nutritional problems and presence of other comorbity diseases as anemia, hypertension and diabetes that can contribute to increase the oxidative stress state, accented for the hyperhomocysteinemia. However, the influence of the therapeutical treatment on the oxidative stress has still several controversies. Thus, oxidative stress studies and its relationship with medicaments are very important. The aim of this study was to determine which oxidative stress markers were altered in hemodialysis patients, as well as the influence of erythropoietin, iron, vitamin B12 and folic acid on these markers and in the hematologic parameters and hyperhomocisteinemia. Plasmatic TBARS, erythrocytic GSH, ALA-D enzyme activity, methemoglobin (MHb), homocysteine (Hcy), hemoglobin (Hb) and hematocrit (Ht) of 36 hemodialysis patients (HP) and 20 controls (C) were determined with a prior consent of all subjects. The personal information of each patient was used for additional data as medicaments treatment. The results found in HP in comparison with the C had significant increase (p<0,05) for TBARS, erythrocytic GSH, MHb, and Hcy, as well as significant decrease (p<0,05) of ALA-D activity, Hb and Ht. So, it was evident the oxidative stress occur, alterations in antioxidants defense, hyperhomocysteinemia and anemia. However, significant differences in the oxidative stress markers had not been found when they were related to the use of medicaments, co-morbidities presence, life style, time of hemodialysis and accomplishment of simple activities. Thus, this work demonstrated that beyond alterations in oxidative stress markers as TBARS and GSH, it was also found alterations in the ALA-D enzyme activity and in the MHb. Moreover, it was possible to observe that some medicaments as erythropoietin, vitamin B12 and folic acid can be involved in the increase of GSH levels.